2017
DOI: 10.3846/13923730.2017.1323794
|View full text |Cite
|
Sign up to set email alerts
|

Energy utilizability concept as a retrofitting solution selection criterion for buildings

Abstract: Retrofitting is widely explored as one of the energy conserving opportunities for existing buildings, in which both passive and active solutions are carefully evaluated. However, when different retrofitting solutions are combined and applied to a building, the total energy savings potential, which is less than the sum of the savings from applying the various individual retrofitting solutions, is considerably reduced and the synergies among the various technologies need to be understood and evaluated. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Moreover, the two factors were chosen because several studies (Beradi, 2016;Silva et al, 2016;Gagliano et al, 2015;Refahi and Talkhabi, 2015;Jaffal et al, 2012) have reported on them. Further, these factors have been reported to lead to different temperature reductions in different climatic areas (Yang et al 2017;La Roche and Berardi, 2014). The latter pointed out that, depending on the local climate, both soil depth and leaf area index played different roles in affecting the peak cooling load.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the two factors were chosen because several studies (Beradi, 2016;Silva et al, 2016;Gagliano et al, 2015;Refahi and Talkhabi, 2015;Jaffal et al, 2012) have reported on them. Further, these factors have been reported to lead to different temperature reductions in different climatic areas (Yang et al 2017;La Roche and Berardi, 2014). The latter pointed out that, depending on the local climate, both soil depth and leaf area index played different roles in affecting the peak cooling load.…”
Section: Methodsmentioning
confidence: 99%
“…Sustainable development is becoming more relevant, with recent studies showing that more and more research is being published that relates to sustainability across the whole building life-cycle [1]. Sustainable building design [2], integrated planning for sustainable building [3], climate change challenges [4], solutions to achieve Nearly Zero-Energy Buildings [5], building-integrated green technologies [6], and the assessment of building refurbishment measures [7][8][9] are among the most topical areas of recent research.…”
Section: Introductionmentioning
confidence: 99%